The G-Protein–Coupled Estrogen Receptor Agonist G-1 Inhibits Proliferation and Causes Apoptosis in Leukemia Cell Lines of T Lineage - Torres-López, Liliana; Olivas-Aguirre, Miguel; Villatoro-Gómez, Kathya; Dobrovinskaya, Oxana (Frontiers in Cell and Developmental Biology, 2022)
The G-protein coupled estrogen receptor (GPER) mediates non-genomic action of estrogen. Due to its differential expression in some tumors as compared to the original healthy tissues, GPER has been proposed as a therapeutic target. Accordingly, the non-steroidal GPER agonist G-1, which has often demonstrated marked cytotoxicity in experimental models, has been suggested as a novel anticancer agent for several sensitive tumors. We recently revealed that cell lines derived from acute T lymphoblastic leukemia (T-ALL) express GPER. Here we address the question whether G-1 is cytotoxic to T-ALL. We have shown that G-1 causes early rise of intracellular Ca2+, arrests cell cycle in G2/M, reduces viability and provokes apoptosis in T-ALL cell lines. Importantly, G-1 caused destabilization and depolymerization of microtubules. We assume that it is a disturbance of the cytoskeleton that cause of G-1 cytotoxic and cytostatic effects in our model. The observed cytotoxic effects, apparently, were not triggered by the interaction of G-1 with GPER, as pre-incubation with the highly selective GPER antagonist G-36 was ineffective in preventing the cytotoxicity of G-1. However, G-36 prevented intracellular Ca2+ rise provoked by G-1. Finally, G-1 showed only a moderate negative effect on the activation of non-leukemic CD4+ lymphocytes. We suggest G-1 as a potential antileukemic drug.